2015
DOI: 10.1083/jcb.201407101
|View full text |Cite
|
Sign up to set email alerts
|

Unipotent,Atoh1+ progenitors maintain the Merkel cell population in embryonic and adult mice

Abstract: A novel, unipotent progenitor population in the skin characterized by Atoh1 expression gives rise to Merkel cells both during development and adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 49 publications
3
52
0
Order By: Relevance
“…We also tested alternate Merkel-cell markers in anagen, catagen and telogen. We found that 77% of K8-positive Merkel cells expressed the early marker Atoh1-GFP ( N =391 from 5 mice; Figure 2D; Wright et al , 2015). VGLUT2 immunoreactivity, which is found in mature Merkel cells and touch-dome afferents (Haeberle et al , 2004), co-localized with K8 in 96% of Merkel cells ( N =489 from 5 mice; Figure 2E).…”
Section: Resultsmentioning
confidence: 93%
“…We also tested alternate Merkel-cell markers in anagen, catagen and telogen. We found that 77% of K8-positive Merkel cells expressed the early marker Atoh1-GFP ( N =391 from 5 mice; Figure 2D; Wright et al , 2015). VGLUT2 immunoreactivity, which is found in mature Merkel cells and touch-dome afferents (Haeberle et al , 2004), co-localized with K8 in 96% of Merkel cells ( N =489 from 5 mice; Figure 2E).…”
Section: Resultsmentioning
confidence: 93%
“…These data imply the existence of a Merkel cell precursor that gives rise to new Merkel cells. We recently showed that embryonic Merkel cell precursors express Atoh1 and are unipotent (Wright et al, 2015). However, three lines of evidence suggest that ectopic K8+ cells created by ectopic Atoh1 expression are post-mitotic.…”
Section: Discussionmentioning
confidence: 99%
“…Mature Merkel cells do not express keratinocyte markers (Haeberle et al, 2004;Moll et al, 1995;Wright et al, 2015), and we wondered whether ectopic Atoh1 expression in keratinocytes altered normal marker expression in these cells. Four days postinduction, we found no cells that co-expressed Atoh1 and the general keratinocyte marker K14 (Krt14 -Mouse Genome Informatics; Fig.…”
Section: Inducible Atoh1 Expression Produces Ectopic K8+ Cells In Glamentioning
confidence: 99%
See 1 more Smart Citation
“…There is ongoing cellular turnover in touch domes, with constant production of stratified epithelial keratinocytes and cyclical expansion of terminally differentiated Merkel cells that coincides with anagen regeneration in the hair cycle (17). Genetic fate mapping has shown that the progenitors maintaining these two cell types are found among the K17 + cells in the touch dome (18), with unipotent atonal homolog 1 (Atoh1)-positive progenitors maintaining the Merkel cells (19). However, the signaling pathways involved in touch dome and Merkel cell homeostasis remain unclear.…”
mentioning
confidence: 99%